2021
DOI: 10.9734/jpri/2021/v33i59b34432
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Knowledge and Attitude Regarding Thyroid Disorders among Population in Taif City, Saudi Arabia

Abstract: Background: Thyroid disorders are among the commonest endocrine disorders worldwide. Attention on people's knowledge and awareness about thyroid diseases is very important in helping for early diagnosis and early treatment of these disorders. The aim of this study to assess the degree of knowledge and attitude of thyroid gland and their disordersamong general population in Taif City, KSA. Methodology: A cross-sectional study was conducted on a representative sample of 600 Saudi adults of Taif general pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…However, inhabitants of KSA's central and eastern regions had lower levels of knowledge than other regions, at 44% and 46%, respectively. This comes reasonably expected, as a previous study conducted in KSA showed similar correlations; females had better knowledge than males (56% compared to 44%), the unemployed had the worst level of knowledge at 7.6%, and the marital status did not have a significant correlation [3].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…However, inhabitants of KSA's central and eastern regions had lower levels of knowledge than other regions, at 44% and 46%, respectively. This comes reasonably expected, as a previous study conducted in KSA showed similar correlations; females had better knowledge than males (56% compared to 44%), the unemployed had the worst level of knowledge at 7.6%, and the marital status did not have a significant correlation [3].…”
Section: Discussionsupporting
confidence: 85%
“…Hyperthyroidism is defined by increased thyroid hormone production and thyroid gland secretion. The leading cause of hyperthyroidism is Graves' disease [3]. Thyroid hormone synthesis is reduced in hypothyroidism, which can be primary (caused by a defect in the thyroid gland) or secondary (caused by pituitary or hypothalamic illness).…”
Section: Introductionmentioning
confidence: 99%
“…These findings indicate lower knowledge levels compared to the reports presented in our study. In contrast, a survey conducted in Taif City [1] revealed that the general population exhibited a good level of knowledge.…”
Section: Discussionmentioning
confidence: 84%
“…The thyroid gland is primarily responsible for the secretion of hormones that regulate several physiological processes, such as metabolic rate, cognition, protein synthesis, and the growth and development of children. Additionally, it is responsible for the secretion of calcitonin, an essential hormone involved in the regulation of calcium homeostasis [1]. Both insufficient and excessive levels of iodine have the potential to interfere with the production of thyroid hormones [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Hypothyroidism, the most prevalent kind of thyroid dysfunction, affects 4 to 5% of people in developed countries. While more than 12% of the US population develops thyroid malfunction during their life every 5 years, all persons aged 35 and above should be examined for thyroiddiseases (Issa et al, 2021). Previous Saudi researchers found that the knowledge regarding risk-factors and prevention of thyroid illnesses among the Saudi general community was poor in 2019 (Alyahya et al, 2021).…”
Section: Introductionmentioning
confidence: 99%